Competitive effects between rainbow trout and Atlantic salmon in natural and artificial streams. Issue 2 (4th December 2014) - S. Houde, Aimee Lee; Smith, Andrew D.; Wilson, Chris C.; Peres‐Neto, Pedro R.; Neff, Bryan D.
Abstract: Competition with non‐native species may impede the restoration of native species, but differences in competitive abilities among intraspecific native populations may make some populations more suitable for reintroduction than others. Here, juvenile Atlantic salmon ( Salmo salar ) from two allopatric populations (LaHave and Sebago) being used for reintroduction into Lake Ontario were placed into two natural stream sites differing in the presence of ecologically similar rainbow trout ( Oncorhynchus mykiss ). We assessed the effects of competition in the natural streams on fitness‐related traits and habitat use of the Atlantic salmon. We then compared these effects to those observed in artificial streams from a previous study. Atlantic salmon in natural streams had reduced fitness‐related traits that were associated with suboptimal microhabitats in the presence of rainbow trout, but utilised optimal microhabitats in their absence. In the presence of rainbow trout, the two Atlantic salmon populations exhibited comparable recapture proportions to each other, but the individuals from the Sebago population had better performance (body size and condition) than those from the LaHave population. Responses of both Atlantic salmon populations to competition with rainbow trout were generally similar in both direction and magnitude when compared to results from the artificial stream study. The combined results suggest that native species restoration efforts should be focused on candidate populations that are ecologically suitable to reintroduction environments, as well as on suitable habitats that do not contain exotic competitors. Moreover, this study highlights the value of controlled experiments in artificial environments for predicting fitness‐related performance in natural environments.